Life-cycle economic analysis of distributed manufacturing with open-source 3-D printers - Wittbrodt, B.T.; Glover, A.G.; Laureto, J.; Anzalone, G.C.; Oppliger, D.; Irwin, J.L.; Pearce, J.M. (Mechatronics (Oxford), 2013)
•Open-source 3-D printers makes distributed manufacturing technically feasible.•Self-replicating rapid prototypers (RepRaps) can manufacture half of their own parts.•Life-cycle economic analysis of RepRap technology for US household provided.•Open-source 3-D printers recover material costs in less than 1year, >200% ROI.•Open-source designs growing exponentially predicts distributed manufacturing scaling. The recent development of open-source 3-D printers makes scaling of distributed additive-based manufacturing of high-value objects technically feasible and offers the potential for widespread proliferation of mechatronics education and participation. These self-replicating rapid prototypers (RepRaps) can manufacture approximately half of their own parts from sequential fused deposition of polymer feedstocks. RepRaps have been demonstrated for conventional prototyping and engineering, customizing scientific equipment, and appropriate technology-related manufacturing for sustainable development. However, in order for this technology to proliferate like 2-D electronic printers have, it must be economically viable for a typical household. This study reports on the life-cycle economic analysis (LCEA) of RepRap technology for an average US household. A new low-cost RepRap is described and the costs of materials and time to construct it are quantified. The economic costs of a selection of 20 open-source printable designs (representing less than 0.02% of those available), are typical of products that a household might purchase, are quantified for print time, energy, and filament consumption and compared to low and high Internet market prices for similar products without shipping costs. The results show that even making the extremely conservative assumption that the household would only use the printer to make the selected 20 products a year the avoided purchase cost savings would range from about $300 to $2000/year. Assuming the 25h of necessary printing for the selected products is evenly distributed throughout the year these savings provide a simple payback time for the RepRap in 4months to 2years and provide an ROI between >200% and >40%. As both upgrades and the components that are most likely to wear out in the RepRap can be printed and thus the lifetime of the distributing manufacturing can be substantially increased the unavoidable conclusion from this study is that the RepRap is an economically attractive investment for the average US household already. It appears clear that as RepRaps improve in reliability, continue to decline in cost and both the number and assumed utility of open-source designs continues growing exponentially, open-source 3-D printers will become a mass-market mechatronic device.